Mechanical force can fine-tune redox potentials of disulfide bonds - Baldus, Ilona Beatrice; Gräter, Frauke (Biophysical journal, 2012)
Mechanical force applied along a disulfide bond alters its rate of reduction. We here aimed at quantifying the direct effect of force onto the chemical reactivity of a sulfur-sulfur bond in contrast to indirect, e.g., steric or mechanistic, influences. To this end, we evaluated the dependency of a disulfide bond's redox potential on a pulling force applied along the system. Our QM/MM simulations of cystine as a model system take conformational dynamics and explicit solvation into account and show that redox potentials increase over the whole range of forces probed here (30-3320 pN), and thus even in the absence of a significant disulfide bond elongation (<500 pN). Instead, at low forces, dihedrals and angles, as the softer degrees of freedom are stretched, contribute to the destabilization of the oxidized state. We find physiological forces to be likely to tune the disulfide's redox potentials to an extent similar to the tuning within proteins by point mutations.
Published online: December 16, 2011
Gesehen am 26.10.2018